2001
DOI: 10.1002/1097-4644(20010401)81:1<128::aid-jcb1029>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the caspase cascade during Stx1-induced apoptosis in Burkitt's lymphoma cells

Abstract: Shiga toxin 1 (Stx1) produced by Escherichia coli has been reported to induce apoptosis in many different cell types, including Burkitt's lymphoma (BL) cells. Since it has been established that the caspases play essential roles as the effector molecules in the apoptotic process in most cases, we examined the kinetics of caspase activation during the process of Stx1-mediated apoptosis of BL cells. Using Ramos BL cells that are highly sensitive to Stx1-mediated cytotoxicity, we observed that multiple caspases, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
31
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 68 publications
4
31
0
Order By: Relevance
“…These data are the first to show that a cell can be resistant to one CD77 ligand and sensitive to another and that a glycosphingolipid can mediate two different cell death pathways. Our data confirm previous reports that caspases are involved in VT-1-induced apoptosis (18,19,37). We also showed that VT-1 triggered mitochondrial changes that, in part, rely on caspase-8 activation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data are the first to show that a cell can be resistant to one CD77 ligand and sensitive to another and that a glycosphingolipid can mediate two different cell death pathways. Our data confirm previous reports that caspases are involved in VT-1-induced apoptosis (18,19,37). We also showed that VT-1 triggered mitochondrial changes that, in part, rely on caspase-8 activation.…”
Section: Discussionsupporting
confidence: 92%
“…Recent reports have shed light on both toxin-and anti-Gb3/CD77 mAb-induced apoptotic pathways (6,18,19), but various questions remain unresolved: Is ligand binding to Gb3/CD77 sufficient to induce apoptosis? Do ligands trigger a single intracellular mechanism?…”
mentioning
confidence: 99%
“…However, recent studies have shown that the B-subunit also has biological effects on target cells through a mechanism mediated by intracellular signals upon binding to Gb3 (Katagiri et al, 1999;Kiyokawa et al, 2001;Mangeney et al, 1993;Mori et al, 2000;Taga et al, 1997). Although Stx1-B-induced intracellular signals are known to mediate apoptosis in Burkitt's lymphoma cells, their biological effect on other cell species has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Fujii et al (12) reported that Stxinduced HeLa cell apoptosis occurs via a pathway requiring caspase-8, -6, and -3, but not caspase-9. In contrast to studies using holotoxin molecules, binding toxin receptors with purified Stx B-subunits or anti-Gb 3 antibodies has been reported to be sufficient to induce caspase-8 activation and apoptosis in Burkitt's lymphoma cells (20). Finally, it is unknown whether Stxs directly activate apoptosis in all cell types or if additional host factors are required in some instances.…”
mentioning
confidence: 91%